Seeds in Chernobyl: the database on proteome response on radioactive environment - Klubicová, Katarína; Vesel, Martin; Rashydov, Namik; Hajduch, Martin (Frontiers in Plant Science, 2012)
Two serious nuclear accidents during the last quarter century (Chernobyl, 1986; Fukushima 2011) contaminated large agricultural areas with radioactivity. The database “Seeds in Chernobyl” http://www.chernobylproteomics.sav.sk contains the information about the abundances of hundreds of proteins from on-going investigation of mature and developing seed harvested from plants grown in radioactive Chernobyl area. This database provides a useful source of information concerning the response of the seed proteome to permanently increased level of ionizing radiation in a user-friendly format.